Novel translational phenotypes and biomarkers for creatine transporter deficiency. Issue 2 (3rd July 2020) - Mazziotti, Raffaele; Cacciante, Francesco; Sagona, Giulia; Lupori, Leonardo; Gennaro, Mariangela; Putignano, Elena; Alessandrì, Maria Grazia; Ferrari, Annarita; Battini, Roberta; Cioni, Giovanni; Pizzorusso, Tommaso; Baroncelli, Laura
Abstract: Creatine transporter deficiency is a metabolic disorder characterized by intellectual disability, autistic-like behaviour and epilepsy. There is currently no cure for creatine transporter deficiency, and reliable biomarkers of translational value for monitoring disease progression and response to therapeutics are sorely lacking. Here, we found that mice lacking functional creatine transporter display a significant alteration of neural oscillations in the EEG and a severe epileptic phenotype that are recapitulated in patients with creatine transporter deficiency. In-depth examination of knockout mice for creatine transporter also revealed that a decrease in EEG theta power is predictive of the manifestation of spontaneous seizures, a frequency that is similarly affected in patients compared to healthy controls. In addition, knockout mice have a highly specific increase in haemodynamic responses in the cerebral cortex following sensory stimuli. Principal component and Random Forest analyses highlighted that these functional variables exhibit a high performance in discriminating between pathological and healthy phenotype. Overall, our findings identify novel, translational and non-invasive biomarkers for the analysis of brain function in creatine transporter deficiency, providing a very reliable protocol to longitudinally monitor the efficacy of potential therapeutic strategies in preclinical, and possibly clinical, studies. Abstract : Creatine transporter deficiency is an orphan disorder characterized by intellectual disability, autistic-like behaviour and epilepsy. Mazziotti et al. identified quantitative biomarkers of translational value for monitoring disease progression and response to therapeutics. Graphical Abstract: